THE MODEL OF FORMATION OF METASUBJECT EDUCATIONAL OUTCOMES OF STUDENTS IN THE SCHOOL - Svetlana Valentinovna Dmitrieva (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the meta-subject as a concept, the appearance of which is due to a number of problems in the modern education system. Attention is drawn to the existing science of determining metapredicate, as well as discrepancies related to the concept of "meta-subject educational results" and "study skills". The proposed definition of metasubject educational results. Identified, described and structured components, which underlie the models offormation of metasubject educational outcomes of students based on the principles of a systematic approach.